Analisis Ketersediaan Air sebuah Das Menggunakan Model NAM (Nedbor Afstromnings Model) - Sumiyati Sumiyati; Sahid Santoso (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
This study was conducted at Loning Watershed which is located in Magelang, Central Java and completed with Loning dam. Water yield from watershed is mainly used for water supply of the Loning irrigation area. The optimal parameter of the NAM model were CQOF = 0.001, CLOF = 0.03, CQIF = 0.01, CLIF = 0.999, Umax = 70, Lmax = 500, CBFL = 0.99, CLG = 0.675, CKBFU = 0.35, CKBFL = 59, CKI = 0.1, and CK2 = 0.1. The optimal initial value for some variables were Qif1+Qof1 = 0.5, Qif2+Qof2 = 0.01, U = 45, L = 480, BFU1 =5.55, and BFL1 = 0.45. Verification of the model indicated that statistically and graphically the NAM model is suitable to be applied for small watersheds for prediction of available water for irrigation as well. The prediction of available water for irrigatin of Loning irrigation area during the planting period of 1999/2000 indicated that there was excess of water during the period of October 1 to July 1. In contrary, lack of water was occurred during the period of July II to September II